Pathogenomes and virulence profiles of representative big six non-O157 serogroup Shiga toxin-producing Escherichia coli - Kalalah, Anwar A.; Koenig, Sara S. K.; Bono, James L.; Bosilevac, Joseph M.; Eppinger, Mark (Frontiers in Microbiology, 2024)
Shiga toxin (Stx)-producing Escherichia coli (STEC) of non-O157:H7 serotypes are responsible for global and widespread human food-borne disease. Among these serogroups, O26, O45, O103, O111, O121, and O145 account for the majority of clinical infections and are colloquially referred to as the "Big Six". The "Big Six" strain panel we sequenced and analyzed in this study are reference type cultures comprised of six strains representing each of the non-O157 STEC serogroups curated and distributed by the American Type Culture Collection (ATCC) as a resource to the research community under panel number ATCC MP-9. The application of long-and shortread hybrid sequencing yielded closed chromosomes and a total of 14 plasmids of diverse functions. Through high-resolution comparative phylogenomics, we catalogued the shared and strain-specific virulence and resistance gene content and established the close relationship of serogroup O26 and O103 strains featuring flagellar H-type 11. Virulence phenotyping revealed statistically significant differences in the Stx-production capabilities that we found to be correlated to the strain's individual stx-status. Among the carried Stx1a, Stx2a, and Stx2d phages, the Stx2a phage is by far the most responsive upon RecA-mediated phage mobilization, and in consequence, stx2a+ isolates produced the highest-level of toxin in this panel. The availability of high-quality closed genomes for this "Big Six" reference set, including carried plasmids, along with the recorded genomic virulence profiles and Stx-production phenotypes will provide a valuable foundation to further explore the plasticity in evolutionary trajectories in these emerging non-O157 STEC lineages, which are major culprits of human food-borne disease.